The Role of Informal Learning in College Jazz Education in Ecuador: Contextualizing Students’ Musical Capital - Merino, Marcos; Ramón Calvi, Juan Carlos (Harmonia: Journal of Arts Research and Education, 2024)
College music education was introduced in Ecuador without first establishing a formal training system for students to reach that educational level. Consequently, many students enter university without having undergone formal music studies, relying instead on informal learning. This study explores the role of informal learning within the context of a university degree in musical performance in Ecuador. To this end, an educational innovation project was implemented at Universidad de las Americas (Quito, Ecuador). Two questionnaires and interviews were used to collect data about the link between the project’s methodology and the students’ prior training. The results indicate that implementing a methodology aligned with students’ previous experiences increases motivation levels for studying music. Therefore, it is concluded that there is a need to reevaluate certain practices associated with informal learning within the framework of higher music education, particularly in countries where the educational structure is not fully developed.